Promoting EFL learners’ exposure to multiculturalism using Skype in the classroom – a case study - Khang D. Nguyen; Van T. T. Phan (Educational Role of Language Journal, 2020)
The study aims at indicating the effectiveness of employing Skype in the classroom to promote chances for EFL learners to expose to multiculturalism. Action research was carried out via a one-year case study on a teacher-participant. The data was collected by observation during Skype connections, the participant’s reflections before and after the connections, and interview of the teacher-participant for his reflections for enhancing his learners’ chances for acquiring multiculturalism. The findings of the study showed that Skype benefited the teacher-participant in facilitating multiculturalism in EFL learning contexts, how Skype could be useful for multicultural connections, and the development of learners’ common curiosity about other cultures through the exposure to multiculturalism.